ANALISIS KINERJA SIMPANG EMPAT BERSINYAL MENGGUNAKAN METODE PKJI 2023 DENGAN PTV VISSIM : (Studi Kasus: Simpang Samsat Kota Bandung) - Wandira, Wiraga; Saepudin, Uu; Martha, Taufik (Jurnal Ilmiah Teknik Sipil, 2026)
The growth and development of a city can be observed through the condition of its transportation system. Bandung, as a metropolitan area, faces complex transportation challenges, particularly at the Samsat signalized four-legged intersection, which serves as a convergence point for traffic flows from various directions. The high traffic volume and a red light duration of up to 5 minutes cause long queues around the intersection, especially during peak hours. This study aims to evaluate the performance of the Samsat signalized intersection in Bandung and identify alternative solutions to improve its performance.This research applies a quantitative approach using direct field observation. The research data consist of both primary and secondary sources. Primary data were obtained through direct observation, while secondary data were collected from relevant institutions such as the Central Statistics Agency.The analysis using PKJI 2023 indicated an average intersection delay of 182.21 seconds/smp with a Level of Service (LOS) F, while the PTV Vissim simulation showed an average delay of 126.30 seconds/vehicle with the same service level, LOS F. The alternative solution proposed was the construction of both a flyover and an underpass. The flyover was planned from Ibrahim Adjie Street (north) to Soekarno Hatta Street (west), while the underpass was planned along Soekarno Hatta Street. Modeling results demonstrated that this development effectively reduced the average queue length from 254.14 meters to 15.34 meters and decreased the average delay from 126.30 seconds/vehicle to 19.52 seconds/vehicle. The service level improved from LOS F to LOS B.The most significant improvement occurred on the west approach (Soekarno Hatta Street), which improved from LOS F to LOS A, followed by performance enhancements on the east approach (Soekarno Hatta Street), the south approach (Ibrahim Adjie Street), and the north approach (Ibrahim Adjie Street).